Financial sector development and growth: The Chinese experience - Iftekhar Hasan; Mingming Zhou (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper documents the financial and institutional developments of China during the past two decades, when China was successfully transformed from a rigid centralplanning economy to a dynamic market economy following its unique path. We empirically examine the relationship between financial development and economic growth in China by employing a panel sample covering 31 Chinese provinces during the important transition period 1986-2002. Our evidence suggests that the development of financial markets, institutions, and instruments have been robustly associated with economic growth in China. – institutions ; growth ; financial intermediation ; transition ; China
Keywords: G30; G10; O16; K40; 330; Finanzsektor; Öffentliches Unternehmen; Privatwirtschaft; Direktinvestition; Regionales Wachstum; Systemtransformation; China